Effect of empagliflozin beyond glycemic control: Cardiovascular benefit in patients with type 2 diabetes and established cardiovascular disease - Monteiro, P (2019)
The prevalence of type 2 diabetes (T2D) continues to increase, and its association with cardiovascular (CV) disease has led to the inclusion of CV endpoints in clinical trials on the treatment of T2D. This article explores the various trials already performed and under development in this field, with particular focus on the EMPA-REG OUTCOME trial. In this trial, empagliflozin, a sodium-glucose co-transporter 2 inhibitor, demonstrated a reduction in CV risk in patients with T2D and established CV disease, in addition to CV safety and a decrease in glycated hemoglobin. This represents a paradigm shift that has led to changes in the international guidelines for the treatment of T2D. These results were maintained in subsequent subgroup analysis for heart failure, chronic kidney disease and peripheral arterial disease, although there are many questions concerning the mechanisms involved in these effects, including whether they are hemodynamic, metabolic or due to decreased myocardial cytoplasmic sodium concentrations. With this reduction in risk for major CV events in patients with T2D, the EMPA-REG OUTCOME trial demonstrated CV protection from a hypoglycemic drug for the first time, and opened a new era in the treatment and management of T2D. This study has led to the development of ongoing trials that will establish which patients will benefit most from this therapy, particularly with regard to comorbidities.